STUDI KARAKTERISTIK TRIBOLOGI DENGAN METODE PIN-ON-DISK PADA POLIURETANA DAN POLITETRAFLUOROETILENA - Sabina Aurellia, Raisa
In various industrial applications it often involves the relative motion of sliding or rotating surfaces which makes the science of tribology very important. Type of polymer that is often used in tribological applications are polyurethane (PU) and polytetrafluoroethylene (PTFE). In this study, the wear test and friction coefficient test were carried out using the pin-on-disk method to determine the wear resistance and friction coefficient values of PU and PTFE. In the testing, PU and PTFE acted as disks that would rotate and contacted with the pin. The test was carried out by varying the test conditions into three types: two-body wear, twobody abrasive wear, and three-body abrasive wear. In the two-body wear condition, a tungsten carbide ball pin was used, while in the two-body abrasive wear condition, an abrasive pin made of a mixture of polyester resin and alumina powder was used. For the three-body abrasive wear condition, a tungsten carbide ball pin was used, and a slurry of water and alumina powder mixture that acted as the third body. Based on the research results, it is known that PTFE exhibits better wear resistance compared to PU. Both PU and PTFE have the best wear resistance in the three-body abrasive wear condition. It is also known that PTFE has a lower coefficient of friction than PU and the two-body abrasive wear condition produce the highest friction coefficient values.